Advanced diffuse hepatic angiosarcoma treated successfully with TACE and targeted immunotherapy: A case report - Lin, Yucheng; Chen, Zheng; Yang, Jianchuan; Lin, Ying; Chen, Sheng; Xie, Ying; Wu, Songsong (Frontiers in Oncology, 2023)
Primary hepatic angiosarcoma (PHA), a rare soft tissue tumor, accounts for only 2% of all liver malignancies. Pathologically challenging, PHA is difficult to be distinguished from other malignancies with ultrasound, Computed Tomography (CT), or Magnetic Resonance Imaging (MRI). Due to late diagnosis and resistance against traditional chemotherapy and/or radiotherapy, only 3% of PHA patients can survive up to two years after diagnosis. To our best knowledge, this case report presents the first case of an advanced diffuse PHA with ruptured hemorrhage that has been effectively treated with TACE and Anlotinib plus Camrelizumab. So far, the patient has received 10 cycles of treatment and is faring well. Latest MRI results show that the tumor has shrunk by 56% and can be assessed as a partial response (PR). This case report includes our experience in treating such a advanced malignancy, and we hope that larger studies on advanced PHA can better quantify the potential benefit.